Gestational diabetes prevention and treatment: a protocol for developing core outcome sets - Eugene Dempsey; Aoife Maria Egan; Fidelma P Dunne; Linda M Biesty; Delia Bogdanet; Caroline Crowther; Narjes Fhelelboom (BMJ Open)
Introduction Selective reporting bias, inconsistency in the chosen outcomes between trials and irrelevance of the chosen outcomes for women, limit the efficiency and value of research for prevention and treatment of gestational diabetes mellitus (GDM). One way to address these challenges is to develop core outcome sets (COSs).Methods and analysis The aim of this manuscript is to present a protocol for a study to develop COSs for GDM prevention and treatment. This is a three-phase project consisting of (1) a systematic review of the literature to create two lists of outcomes that have been reported in trials and systematic reviews of trials of interventions for the prevention and treatment of GDM, (2) a three-round, web-based e-Delphi survey with key stakeholders to prioritise these outcomes and (3) a consensus meeting to resolve any remaining disagreements and to agree on two COSs.Ethics and dissemination Ethical approval to conduct this study was obtained from the ethics committee at Galway University Hospitals on 13 December 2018 (Reference: C.A.2078). We will disseminate our research findings through peer-reviewed, open access publications and present at international conferences to reach a wide range of knowledge users.